Revision history of "Recurrence relation of exponential integral E"

Jump to: navigation, search

Diff selection: Mark the radio boxes of the revisions to compare and hit enter or the button at the bottom.
Legend: (cur) = difference with latest revision, (prev) = difference with preceding revision, m = minor edit.

  • (cur | prev) 00:23, 8 August 2016Tom (talk | contribs). . (399 bytes) (+399). . (Created page with "==Theorem== The following formula holds for $n=1,2,3,\ldots$: $$E_{n+1}(z)=\dfrac{e^{-z}-zE_n(z)}{n},$$ where $E_n$ denotes the exponential integral E. ==Proof== ==Refer...")